Application of Behavioral Counseling with Reward and Punishment Techniques in Handling Violation of Student Rules - Lubis, Aulia Muflih; Lubis, Saiful Akhyar; Damayanti, Nefi (Yana Research, 2023)
The purpose of this study was to determine the application of behavioral counseling with reward and punishment techniques in dealing with violations of the rules on students at Subulussalam Sayurmaincat Kotanopan. The research methodology in this study was PTBK, namely the research was conducted through two cycles. Each cycle I and II consists of four stages, namely: the planning stage, the action/implementation stage, the observation stage, the reflection stage. The subjects of this study were 15 students of Class XI MA Subulussalam Sayurmaincat Kotanopan. The results of this study indicate that the application of behavioral counseling with reward and punishment techniques can handle violations of the rules of conduct for students in Subulussalam Sayur Maincat, Nopan City. Through the application of Behavioral counseling with Reward and Punishment techniques, it is possible to handle students who violate the rules at MA Subulus salam Sayur Maincat Nopan City. Of the 15 students before being given the application of Behavioral counseling with Reward and Punishment techniques in dealing with students who violated the rules in the MA Subulussalam Sayur Maincat Kotanopan school, violations of the rules were still quite high. Furthermore, after being given the application of behavioral counseling with reward techniques in the form of praise and gifts both verbally and non-verbally, also given punishment in the form of memorizing youth oaths, their truant behavior can be reduced and they can be handled properly.